'Triangulating' AMPATH: Demonstration of a multi-perspective strategic programme evaluation method - Thomas S Inui; John E Sidle; Winstone M Nyandiko; Violet N Yebei; Richard M Frankel; David L Mossbarger; David Ayuku; Joyce Ballidawa; Rose Ayikukwei (Taylor & Francis Group, 2009)
Clinical programmes are typically evaluated on operational performance metrics of cost, quality and outcomes. Measures of patient satisfaction are used to assess the experience of receiving care, but other perspectives, including those of staff and communities, are not often sought or used to assess and improve programmes. For strategic planning, the Kenyan HIV/AIDS programme AMPATH (Academic Model Providing Access to Healthcare) sought to evaluate its performance in 2006. The method used for this evaluation was termed 'triangulation,' because it used information from three different sources - patients, communities, and programme staff. From January to August 2006, Indiana University external evaluators and AMPATH staff gathered information on strengths, weaknesses and suggestions for improvement of AMPATH. Activities included in-depth key-informant semi-structured interviews of 26 AMPATH clinical and support staff, 56 patients at eight clinic sites, and seven village health dialogues (mabaraza) at five sublocations within the AMPATH catchment area. Data sources included field notes and transcripts of translated audio recordings, which were subjected to qualitative content analysis. Eighteen recommendations for programme improvement emerged, including ten from all three respondent perspectives. Three recommendations were cited by patients and in mabaraza, but not by staff. Triangulation uncovered improvement emphases that an internal assessment would miss. AMPATH and Kenyan Ministry of Health leadership have deliberated these recommendations and accelerated strategic change actions, including rural satellite programmes, collaboration with village-based workers, and door-to-door village-based screening and counselling.